Minat Siswa Mengikuti Ekstrakurikuler Cabang Olahraga Petanque di SMK Negeri 4 Kota Jambi - Addin, Muhammad Nur; Indrayana, Boy; Murniati, Sri (MAN Insan Cendekia Jambi, 2025)
This study aims to analyze the level of student interest in participating in extracurricular sports Petanque at SMK Negeri 4 Jambi City. The research method used is descriptive quantitative with data collection techniques through questionnaires. The research sample consisted of students who participated in extracurricular Petanque at the school. The results showed that student interest in extracurricular Petanque was in the high category with a percentage of 37.46%. This interest is influenced by intrinsic and extrinsic factors. Intrinsic factors include student interest, attention, and involvement in activities, with a moderate category and a percentage of 34.67%. Meanwhile, extrinsic factors consisting of the environment and the availability of tools and facilities have a significant influence on student interest, with a high category and a percentage of 43.54%. Based on these results, it can be concluded that extrinsic factors have an important role in increasing student interest, especially through the provision of adequate facilities. However, intrinsic factors still need to be improved, especially in terms of student interest in Petanque sports. Therefore, efforts are needed such as more interesting training, wider promotion, and increasing student involvement in extracurricular activity.